Preface: Education as an Opportunity - Daniele, Franca (European Scientific Journal, ESJ, 2021)
On December 10th, 2020 The First Educational Science Conference organized by the European Scientific Institute was held online due to the COVID-19 pandemic that has been afflicting the whole world for some months now. Nonethless, the world continues to live, the world continues to produce, people continue to work, researchers continue to search, teachers continue to teach. The United Nations recognized the right for education for all and has recently set some of the goals for education – Goal 4.7 states “By 2030, ensure that all learners acquire the knowledge and skills needed to promote sustainable development, including, among others, through education for sustainable development and sustainable lifestyles, human rights, gender equality, promotion of a culture of peace and non-violence, global citizenship and appreciation of cultural diversity and of culture’s contribution to sustainable development” (www.un.org., 2021)